Analisis Persepsi Siswa atas Penguasaan TPACK Guru dan Efektivitas Pembelajaran Daring terhadap Kepuasan Belajar Ekonomi - Elli Setianingsih; Ferry Setyowibowo; Dini Octoria (Departement of Mathematics Education, 2024)
This study aims to identify and analyze (1) the effect of students' perceptions of teachers' TPACK mastery on Economics learning satisfaction at SMAN 2 Sukoharjo, (2) the effect of the effectiveness of online learning on Economics study satisfaction at SMAN 2 Sukoharjo, (3) the effect of student perceptions of teacher TPACK mastery and the effectiveness of online learning on Economics study satisfaction at SMAN 2 Sukoharjo. This research is a quantitative study with a population of 144 students in class XI IPS 1, XI IPS 2, XI IPS 3, XI IPS 4. The sampling technique used is non-probability sampling. Collecting data using a questionnaire or questionnaire and analysis of the data used is descriptive statistical analysis and hypothesis testing (multiple regression analysis. The results of this study indicate that (1) there is a positive and significant influence among students' perceptions of teacher TPACK mastery on Economics learning satisfaction at SMAN 2 Sukoharjo. (2) there is a positive and significant influence between the effectiveness of online learning on the satisfaction of studying Economics at SMAN 2 Sukoharjo. (3) there is a positive and significant influence between students' perceptions of teacher TPACK mastery and the effectiveness of online learning on Economics learning satisfaction at SMAN 2 Sukoharjo..